2014
DOI: 10.1007/s13762-014-0715-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of continuous lead removal from aqueous solutions by marble wastes: efficiencies and mechanisms

Abstract: Lead removal from synthetic solutions and real wastewater by Bianco Gioia marble wastes as abundant, renewable and eco-friendly materials was studied under different experimental conditions in a continuous stirring tank reactor. These marble wastes were found to be very efficient in removing lead for several experimental situations. Indeed, for initial aqueous pH values higher than 3.6, a lead removal efficiency of about 100 % was achieved even for high aqueous concentrations (200 mg L -1 ), important feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Various technologies have been tested such as chemical precipitation, ion exchange, reverse osmosis and membrane filtration (Mlayah and Jellali, 2015). Even if these methods are relatively efficient in removing heavy metals under certain experimental conditions, they are found to be very expensive since they require high capital, operational and maintenance costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various technologies have been tested such as chemical precipitation, ion exchange, reverse osmosis and membrane filtration (Mlayah and Jellali, 2015). Even if these methods are relatively efficient in removing heavy metals under certain experimental conditions, they are found to be very expensive since they require high capital, operational and maintenance costs.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has also the main advantage of reducing the production of chemical and/or biological sludge and offering the possibility of the adsorbents regeneration and metal recovery for a further subsequent use. Several organic and mineral materials have been efficiently tested for lead removal from aqueous solutions such walnut sawdust (Bulut and Tez, 2007), activated carbon originated from cow bone (Cechinel et al, 2013), peanut shell's biochar , Fe-and Al-based water treatment residues and dead calcareous skeletons (Lim and Aris, 2014) and powdered marble wastes (Mlayah and Jellali, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Figure (6) shows that the removal efficiency of Cu +2 and Ni +2 by 7g/l SSH dosage were about 92.5% and 84.8% for single system and decreases to 86.5%and75.6 % for binary system. These results indicated that the metal removal efficiency was greater in the single systems as comprised with the multi component one; this may be due to the absence of competitive processes between metals and sorbent mass in single component system [10]. The removal efficiency of Cu +2 was higher than that of Ni +2 .…”
Section: Effect Of Sunflower Seed Husk Dosagementioning
confidence: 86%
“…The World Health Organization recommends the concentration of lead in drinking water to be under 0.1 mg/L [9], and different technologies have been developed to minimize its presence, including those based on precipitation [10], ion exchange [11], inverse osmosis [12], coagulation [13], electrodialysis [14], ultrafiltration [15], and supported liquid membranes [2]. However, all of these require large energy inputs, which is inefficient, and none is able to completely remove it [16,17].…”
Section: Introductionmentioning
confidence: 99%